Territorial governance and sustainability: a multimodal approach - Cheema, Abdur Rehman; Mehmood, A. (Edward Elgar Publishing, 2025)
This chapter presents a “multimodal” approach to territorial governance, aiming to bridge the gap between global sustainability agendas and local action. While aligning with national aspirations, translating these agendas into actionable local strategies faces challenges in capacity, information access, and governance effectiveness. Multimodal territorial governance, it argues, addresses these challenges by emphasising local nuances, community engagement, and intergovernmental collaboration, particularly pertinent in developing countries like Pakistan. The chapter looks at Pakistan's experience with the Sustainable Development Goals to highlight both the potential and the barriers associated with their localisation and implementation. The country has made limited progress, partly due to spending the early years on framework development and public sector capacity-building. Access to data has further complicated the measurement of progress. In this situation, the multimodal territorial governance approach offers opportunities for effectively understanding and implementing the sustainability objectives by accommodating local context, engaging communities, and fostering collaboration.